Construction cost control: A review of practices in Malaysia - Bahaudin, Ahmad Yusni; Mohamed Elias, Ezanee; Dahalan, Hishamuddin; Jamaludin, Roslan (2012)
Construction project cost control has often been subjected to a myriad of studies, but these studies are often circulated around the scope of corrective project control. The conventional cost control system is basically corrective based, where the cost overruns have already been incurred and the company may have experienced losses, which is a little too late.The weakest form of cost control will be where the cost reports for a particular project are unable to make corrections for cost deviations incurred in that project but maybe useful for upcoming projects.In other words, it is already too late for corrective actions to be performed because the project or the particular activity has been completed.The elements of the conventional cost control system are observation, comparison of observation with some desired standard and finally corrective action to be taken.This paper attempts to identify the cost control methods and procedures that construction practitioners in Malaysia are currently utilising and aims to get feedback from the respondents whether the current approach and techniques are adequate or whether a new approach to cost control as an alternative to the conventional corrective technique is really necessary. A project control system must be able to anticipate emerging or unforeseeable problems, a deviation from the conventional project methods which are often slow where problems may already exist.This research involved face to face interviews with respondents and the methodology is wholly qualitative.The respondents are class G7 contractors registered with the CIDB where some of them are Bursa - Stock Exchange listed companies.The outcome of the research revealed that effective cost control procedures, practices and approaches are seriously lacking and these are no different from practices in some countries.Contractors seem to adopt the strategy of conservatism as far as cost control is concerned and are comfortable with the conventional method of cost control with limited involvement in information technology.